2021
DOI: 10.1007/s12031-021-01845-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship between the miRNA-centered ceRNA Regulatory Network and Fatigue

Abstract: In recent years, the incidence of fatigue has been increasing, and the effective prevention and treatment of fatigue has become an urgent problem. As a result, the genetic research of fatigue has become a hot spot. Transcriptome-level regulation is the key link in the gene regulatory network. The transcriptome includes messenger RNAs (mRNAs) and noncoding RNAs (ncRNAs). MRNAs are common research targets in gene expression profiling. Noncoding RNAs, including miRNAs, lncRNAs, circRNAs and so on, have been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Recent research has revealed that lncRNAs and miRNAs can interact, and thus, affect the posttranscriptional regulation of their targets by inhibiting miRNA activity. 18 Here, miR-490-5p was found to be directly targeted by linc00473. Many studies have shown that miR-490-5p is an important tumor blocker and plays an anti-tumor role involving many key cellular pathways.…”
Section: Sevoflurane Reverses Cisplatin-resistant Phenotype and Decre...mentioning
confidence: 87%
“…Recent research has revealed that lncRNAs and miRNAs can interact, and thus, affect the posttranscriptional regulation of their targets by inhibiting miRNA activity. 18 Here, miR-490-5p was found to be directly targeted by linc00473. Many studies have shown that miR-490-5p is an important tumor blocker and plays an anti-tumor role involving many key cellular pathways.…”
Section: Sevoflurane Reverses Cisplatin-resistant Phenotype and Decre...mentioning
confidence: 87%
“…The ceRNA mechanism proposed that transcripts can bind with microRNA (miRNA) or lncRNA, leading to post‐transcriptional control 10 . Transcripts such as lncRNA or messenger RNA (mRNA) can serve as ceRNAs through miRNA response elements (MRE).…”
Section: Introductionmentioning
confidence: 99%
“…Messenger RNA (mRNA) and non-coding RNA (ncRNA) are the involved transcripts, and mRNA expression profiling has been prevalently studied. Other RNAs, such as microRNA (miRNA), long non-coding RNA (lncRNA), circular RNA (circRNA), have also been extensively researched for the past few years [ 10 ]. Competing endogenous RNA (ceRNA) is receiving increasing attention with the development of the mechanism of post-transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%